2018
DOI: 10.3390/bios8020032
|View full text |Cite
|
Sign up to set email alerts
|

Development of a β-Lactoglobulin Sensor Based on SPR for Milk Allergens Detection

Abstract: A sensitive and label-free surface plasmon resonance (SPR) based sensor was developed in this work for the detection of milk allergens. β-lactoglobulin (BLG) protein was used as the biomarker for cow milk detection. This is to be used directly in final rinse samples of cleaning in-place (CIP) systems of food manufacturers. The affinity assay was optimised and characterised before a standard curve was performed in pure buffer conditions, giving a detection limit of 0.164 µg mL−1 as a direct binding assay. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…This value is low enough to consider this method as an alternative to those commercially established for milk allergen analysis in clean-in-place practices. A maximum value of 2 ppm of β-lactoglobulin has been proposed as a threshold in final rinse waters in clean-in-place practices [19]. Values for the limit of detection in ELISA typically lie in the 1–5 ppm concentration range [20], and limits of detection lower than 0.2 ppm are unusual in commercially available kits [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is low enough to consider this method as an alternative to those commercially established for milk allergen analysis in clean-in-place practices. A maximum value of 2 ppm of β-lactoglobulin has been proposed as a threshold in final rinse waters in clean-in-place practices [19]. Values for the limit of detection in ELISA typically lie in the 1–5 ppm concentration range [20], and limits of detection lower than 0.2 ppm are unusual in commercially available kits [21].…”
Section: Discussionmentioning
confidence: 99%
“…Values for the limit of detection in ELISA typically lie in the 1–5 ppm concentration range [20], and limits of detection lower than 0.2 ppm are unusual in commercially available kits [21]. Recently, electrochemical biosensors developed for food allergen detection with limits of detection ranging from values as low as a few ppbs to ppms have been reported [2,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these biosensors are advantageous in terms of their simplicity of use, label free detection, and real-time monitoring. Ito et al [68] demonstrated the analysis of β-LG using monoclonal antibodies and a flow-based QCM sensor that offered a LOD down to 1 × 10 −3 µg/mL. However, QCM biosensor are facing some limitations in terms of sensitivity, specificity, and excessive interferences [84].…”
Section: Immunosensorsmentioning
confidence: 99%
“…The SPR sensor showed good sensitivity with a LOD of 57.8 × 10 −3 µg/mL, comparable to ELISA. Further, SPR biosensor based on immunoassay has also been developed for β-LG detection [68]. The optimized SPR biosensor was successfully examined for its detection performance, offering excellent sensitivity with 0.164 µg mL −1 LOD.…”
Section: Immunosensorsmentioning
confidence: 99%
“…An optical sensor, a classical sensor type based on optical principles, can sensitively monitor measured information and convert the information into optical signals or other forms of data according to certain rules [1]. Owing to its advantages (e.g., non-contact and non-destructive measurement, little interference and high sensitivity), the optical sensor supports a wide range of applications in the realm of food safety [2,3], environmental monitoring [4], drug testing [5], medical analysis [6,7], biochemical tests [8,9] and so on. The realization and control means of high-sensitivity optical sensors, especially related optical sensor devices, play a key role in optical measurement and biosensors.…”
Section: Introductionmentioning
confidence: 99%